2017
DOI: 10.1016/j.psep.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and substrate removal kinetics in the semi-continuous anaerobic digestion of thermally pretreated two-phase olive pomace or “Alperujo”

Abstract: A study of the semi-continuous anaerobic digestion process of thermally pretreated twophase olive pomace (TPOP) at 120 ºC during 180 minutes was carried out in laboratoryscale completely stirred tank reactors at mesophilic temperature. Organic loading rates (OLR) in the range of 2.0-7.0 g VS/(L·d) were tested after the pretreatment and the breakage of complex organic matter. Total and soluble chemical oxygen demand (CODt and CODs) removal efficiencies decreased slightly between 77.9-71.7% and 92.3-85.0% when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…The application of different types of pre-treatment on wet pomace would be another possibility to improve methane production. Thus, methane production was enhanced by subjecting olive pomace to hydrothermal pre-treatment at 180 • C for 3 h [142]. The pre-treatment provoked a partial breakage of the polymers of the material, which improved its biodegradability.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…The application of different types of pre-treatment on wet pomace would be another possibility to improve methane production. Thus, methane production was enhanced by subjecting olive pomace to hydrothermal pre-treatment at 180 • C for 3 h [142]. The pre-treatment provoked a partial breakage of the polymers of the material, which improved its biodegradability.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…AD of organic waste has been applied extensively for decades to produce biogas and several studies of AD on the OMSW have been reported (de la Lama et al 2017;Gunay and Karadag 2015). However, using OMSW as the sole substrate is not recommended due to its nutritional imbalance (Fernández Rodríguez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On these studies, higher OLRs usually implied the inhibition of the process by the accumulation of volatile fatty acids and phenolic compounds. 35,42,44 Other authors reported operations at much higher OLRs than 1 g VS/(L reactor •d) without compromising reactor performance, although in most of the cases the experimentation time was less than 2 hydraulic retention times per condition, [36][37][38]41 which may not be enough for triggering the inhibition of the anaerobic digestion process.…”
Section: Review Of the Anaerobic Digestion Of Omswmentioning
confidence: 99%
“…2 report a positive increment of the methane production, when the pre-treatment is used and due to the high energy demand of the pre-treatment, the net energy produced is diminished (blue color surface) respect single AD. According to the results, low temperature thermal pre-treatments 27,30,41 and alkaline 24,27 pre-treatments resulted in the largest improvements in the net energy production. The effects of low-intensive pre-treatments are related to the deflocculating of macromolecules, rather than the degradation of fibrous structures.…”
Section: Review Of the Anaerobic Digestion Of Omswmentioning
confidence: 99%